Evaluating the Effects of Dam Construction on the Morphological Changes of Downstream Meandering Rivers (Case Study: Karkheh River) - Liaghat, A.; Adib, A.; Gafouri, H. R. (Engineering, Technology & Applied Science Research, 2017)
The establishment of stability in rivers is dependent on a variety of factors, and yet the established stability can be interrupted at any moment or time. One factor that can strongly disrupt the stability of rivers is the construction of dams. For this study, the identification and evaluation of morphological changes occurring to the Karkheh River, before and after the construction of the Karkheh Dam, along with determining the degree of changes to the width and length of the downstream meanders of the river, have been performed with the assistance of satellite images and by applying the CCHE2D hydrodynamic model. Results show that under natural circumstances the width of the riverbed increases downstream parallel to the decrease in the slope angle of the river. The average width of the river was reduced from 273 meters to 60 meters after dam construction. This 78% decrease in river width has made available 21 hectares of land across the river bank per kilometer length of the river. In the studied area, the average thalweg migration of the river is approximately 340 meters, while the minimum and maximum of river migration measured 53 and 768 meters, respectively. Evaluations reveal that nearly 56% of the migrations pertain to the western side of the river, while over 59% of these migrations take place outside the previous riverbed. By average, each year, the lateral migration rate of the river is 34 meters in the studied area which signifies the relevant instability of the region.